Anti-D prophylaxis for rhesus D (RhD)-negative women having an abortion of a pregnancy up to 13+6 weeks' gestation: a systematic review and new NICE consensus guidelines. Issue 2 (20th January 2020) - Schmidt-Hansen, Mia; Lord, Jonathan; Hawkins, James; Cameron, Sharon; Pandey, Anuja; Hasler, Elise; Regan, Fiona
Abstract : Background: In order to develop the 2019 National Institute for Health and Care Excellence (NICE) national guideline on abortion care for the National Health Service 1 we undertook a systematic review comparing anti-D prophylaxis to no prophylaxis in rhesus D (RhD)-negative women undergoing medical or surgical abortion of pregnancy at ≤13 +6 weeks' gestation Methods: We searched Embase, Medline and the Cochrane Library on 19 October 2018. We also consulted experts and checked reference lists for any missed trials. Eligible studies were randomised controlled trials and non-randomised comparative studies, published in English from 1985 onwards, comparing anti-D prophylaxis to no anti-D prophylaxis in RhD-negative women undergoing medical or surgical abortion at ≤13 +6 weeks' gestation, and reporting subsequent anti-D isoimmunisation/sensitisation or subsequent affected pregnancy. These outcomes were to be analysed as risk ratios in Review Manager 5.3 using the Mantel-Haenszel statistical method and a fixed or random effect model. The overall quality of the evidence was planned to be assessed using GRADE. Results: The search identified 426 potentially relevant studies of which none met the inclusion criteria. Recommendations for practice were therefore based on the clinical expertise of the guideline committee. Conclusions: (1) Offer anti-D prophylaxis to women who are Rhesus D negative who are having an abortion after 10 +0 weeks' gestation. (2) Do not offer anti-D prophylaxis to women who are having a medical abortion up to and including 10 +0 weeks' gestation. (3) Consider anti-D prophylaxis for women who are rhesus D negative and are having a surgical abortion up to and including 10 +0 weeks' gestation.